Manufacturing Company and Its Communication. (2016) - Prajová, Vanessa; Yakimovich, Boris; Tyurin, Ivan; Firsova, Svetlana
Abstract: Modern marketing communication requires more than just making the product target customers. In the modern era, organizations must communicate with their customers by means that are available to them and that search. One of the key tools for integrated marketing communication is the Internet. Creative use of the Internet to disseminate messages of communication contributes to the enhancement of integrated communication for its interactivity, and continuity with globality. In the future it can be expected that interactive marketing communications becomes a crucial form of communication in some areas. Internet marketing is becoming a "superhighway" and therefore is an important medium of integrated marketing communications